Pengaruh Modal Kerja Terhadap Rentabilitas Modal Sendiri Pada Koperasi Pegawai Republik Indonesia (KPRI) Sugri Rangkasbitung - Euis Ajizah; Hurrat Syadlia; Lita Mulyati (E-Journal Studia Manajemen, 2014)
Cooperative hold deposits with the aim that employees can save money, cooperatives can also provide loans to its members under management. This study aims to determine the effect of the efficient use of working capital to own capital profitability on Employee Cooperative Republic of Indonesia (KPRI) Sugri Rangkasbitung. The method used in this research is descriptive method with quantitative approach. This sampling technique purposive sampling method. Based on the product moment correlation coefficient showed an even stronger association between the efficiency of working capital with their own capital profitability. With a coefficient of determination shows the profitability of own capital is affected by the efficiency of working capital. Based on the results of hypothesis testing is known that the efficiency of working capital partially significant effect on the profitability of own capital significance level the hypothesis is accepted.